Fast analysis of capsaicinoids in Naga Jolokia extracts (Capsicum chinense) by high-performance liquid chromatography using fused core columns. (15th January 2018) - Stipcovich, Tea; Barbero, Gerardo F.; Ferreiro-González, Marta; Palma, Miguel; Barroso, Carmelo G.
Highlights: Six major capsaicinoids have been separated by HPLC. A fused core columns has been used. An analysis time of fewer 3 min is needed on using HPLC for the separation. A validation of the method has been developed. The final method was applied in peppers and spicy food samples. Abstract: A rapid high-performance liquid chromatography method with a C18 reverse-phase fused-core column has been developed for the determination and quantification of the main capsaicinoids (nornordihydrocapsaicin, nordihydrocapsaicin, capsaicin, dihydrocapsaicin, homocapsaicin and homodihydrocapsaicin) present in Naga Jolokia peppers. A fused-core Kinetex™ C18 column (50 × 2.1 mm i.d.; 2.6 μm) was used for the analysis. The chromatographic separation was obtained with a gradient method in which the mobile phase was water (0.1% acetic acid) as solvent A and acetonitrile (0.1% acetic acid) as solvent B. The separation of all compounds was achieved in less than 3 min with a total analysis time (sample-to-sample) of 10 min. The robustness of the method was evaluated. The method showed excellent repeatability and intermediate precision expressed as coefficient of variance of less than 2%. The developed method was employed for the quantification of the major capsaicinoids present in different peppers and commercial products containing chilli peppers.